Interrogating anthropomorphism in Benin and northern Edo art: some tentative notes for historical clarifications (2015)
This paper interrogates a rare anthropological collection from Edo North gathered together between 1908 and 1910 by Northcote W. Thomas, first colonial government anthropologist in Nigeria. After collection, the objects have been stored up, largely ignored, at the University of Cambridge, Museum for Archaeology and Anthropology. The paper questions the resultant long time de- contextualisation and isolation of these objects that have, over the time, made it remote to link these evidential materials and their producer culture and neighboring cultures. In an attempt to re-contextualize the objects, a comparison is made, of highly anthropomorphic Benin court art, which has for a long time, politically, dominated Northern Edo land but its character is not represented in Northern Edo art and selected anthropomorphic objects from the Thomas collection. The idea underlying Benin artistic production is basically anthropomorphic, revolving around the Benin king and hierarchy and hence a court art, whereas there is paucity of human representations in Northern Edo land which intriguingly also doesn't have the political structure to support it. Using the older language age evidence of forms of Edo language spoken in Northern Edo land, the paper queries the possibility of a south-north movement to create the works under reference. Perhaps there had been an earlier north-south movement and then a later south-north returnee movement whereby the works in the Thomas collection would represent those of the earlier northern Edo autochthons and ancestors of present day occupants. The Thomas collection may be remnants of an earlier tradition before Benin suzerainty gained full grounds in the 19th Century